2003
DOI: 10.1002/hlca.200390178
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation as Glycosidase Inhibitors of Carbasugar‐Derived Spirodiaziridines, Spirodiazirines, and Spiroaziridines

Abstract: Dedicated to Professor Wolfgang Steglich on the occasion of his 70th birthdayThe spirodiaziridines 6 and 9, potential inhibitors of a-and b-glucosidases, were prepared from the validoxylamine A-derived cyclohexanone 5. The trimethylsilyl protecting groups of 5 are crucial for the formation of 6 in good yields. Oxidation of 6 gave 7. The diaziridine 6 (pK HA 2.6) and the diazirine 7 did not inhibit the b-glucosidases from almonds, the b-glucosidase from Caldocellum saccharolyticum, and the aglucosidase from yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Aziridine-based inhibitors enjoy the theoretical advantage of having a higher initial, noncovalent affinity for a glycosidase active site owing to the positively charged (when protonated) nitrogen atom, which should help direct the inactivator toward the negatively charged active site. The spiroaziridines 9a and 9b were tested against a few different enzymes and shown to be only very weak inactivators of a single β-glucosidase and a single α-glucosidase, respectively, possibly because of the steric demands imposed at the anomeric center (Kapferer et al 2003). Spiroaziridine 9c was shown to be a potent inactivator of one α-galactosidase, although it showed no activity against other enzymes (Tong and Ganem 1988).…”
Section: Epoxide-and Aziridine-based Inactivatorsmentioning
confidence: 99%
“…Aziridine-based inhibitors enjoy the theoretical advantage of having a higher initial, noncovalent affinity for a glycosidase active site owing to the positively charged (when protonated) nitrogen atom, which should help direct the inactivator toward the negatively charged active site. The spiroaziridines 9a and 9b were tested against a few different enzymes and shown to be only very weak inactivators of a single β-glucosidase and a single α-glucosidase, respectively, possibly because of the steric demands imposed at the anomeric center (Kapferer et al 2003). Spiroaziridine 9c was shown to be a potent inactivator of one α-galactosidase, although it showed no activity against other enzymes (Tong and Ganem 1988).…”
Section: Epoxide-and Aziridine-based Inactivatorsmentioning
confidence: 99%
“…A limited number of polyhydroxylated spiroazacycles in which the hydroxyl groups are positioned on a cycloalkane ring has been described in the literature so far. In 2003, Vasella et al reported the synthesis of spiroaziridines 5 (Scheme 1) [19]. These compounds were designed as mechanistic probes to study the impact of the position of the basic nitrogen atom on the inhibition profile towards a panel of glycosidases.…”
Section: Cyclitol-based Azaspiranesmentioning
confidence: 99%
“…[3][4][5] that is used to check and extend the existing assignments. In Table 7 the observed vibrational wavenumbers in each spectrum and the previous assignments from Refs.…”
Section: Vibrational Assignmentmentioning
confidence: 99%
“…Over the last 50 years, the knowledge and understanding of organosilane compounds has increased considerably, and these materials now have applications in nearly all aspects of modern industry (in the clinical testing, pharmaceutical, medical, chemical, research and manufacturing industries) [1,2], trimethylsilyl moiety being the most common protecting group used in organic synthesis [3,4]. Isocyanates are widely used in the manufacture of flexible and rigid foams, fibres, coatings such as paints and varnished, in the automobile industry and building insulation materials but they also have important effects for the health and are classified as potential human carcinogens.…”
Section: Introductionmentioning
confidence: 99%